An Improved Authentication Key Management Scheme for Multihop Relay in IEEE 802.16m Networks - Adnan, Shahid Khan; Norsheila, Fisal; Mazlina, Esa; Sharifah, Kamilah; Sharifah, Hafizah; M., Abbas (IEEE, 2010)
Relaying and cooperation have re-emerged as important research topic in the wireless communication over the past decade. IEEE 802.16m Multihop relay network is assiduously developing to accomplish high capacity services with large cell coverage. Considerable interest currently exists in the exploitation of Relay based Wimax. This is mainly the result of lower infrastructure cost and high data transfer rates compared to existing 3G. However due to lack of physical boundaries and injection of distributed relays, it is known to be more vulnerable to security holes as a trade off. In this paper we propose a new distributed authentication key scheme for Multihop Relays IEEE 802.16m network service. The propose scheme uses decode and forward relays with localized authentication. The scheme works in distributed authentication to authenticate Subscriber station (SS) and Relay stations (RS) at initial network entry. Our new imprpoved distributed scheme utilizes healthy security issues and the Multihop Relay network application features. Both analysis and performance evaluation shows that our scheme can significantly increases the network throughput and reduce the security holes as well as communication overheads.